The implications of institutional specificities on the income inequalities drivers in European Union - Ionut Jianu; Ion Dobre; Dumitru Alexandru Bodislav; Carmen Valentina Radulescu; Sorin Burlacu (Economic Computation and Economic Cybernetics Studies and Research, 2019)
This paper aims to review the different impacts of income inequality drivers on the Gini coefficient, depending on institutional specificities. In this context, we divided the European Union member states in two clusters (the cluster of member states with inclusive institutions / extractive institutions) using the institutional pillar as a clustering criterion. In both cases, we assesed the impact of income inequality drivers on Gini coefficient by using a fixed effects model in order to examine the role and importance of the institutions in the dynamics of income disparities.The models were estimated by applying the Panel Estimated Generalized Least Squares (EGLS) method, this being weighted by Cross-section weights option. The separate assessment of the income inequality reactivity to the change in its determinants according to the institutional criterion represents a new approach in this field of research and the results show that the impact of moderating income inequality strategies is limitedin the case of member states with extractive institutions.
Keywords: D63; E02; I32; 330; income inequality; poverty; institutions; cluster; neets